2017
DOI: 10.11622/smedj.2016172
|View full text |Cite
|
Sign up to set email alerts
|

Developing and validating a localised, self-training mindfulness programme for older Singaporean adults: effects on cognitive functioning and implications for healthcare

Abstract: There is a paucity of research available on the effect of mindfulness on cognitive function. However, the topic has recently gained more attention due to the ageing population in Singapore, catalysed by recent findings on brain function and cellular ageing. Recognising the potential benefits of practising mindfulness, we aimed to develop a localised, self-training mindfulness programme, guided by expert practitioners and usability testing, for older Singaporean adults. This was followed by a pilot study to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…39 Of the four studies that found no effect, three used a web-based application and one applied a DVD program. 36 In addition to the lack of effect on inhibition, Polsinelli et al 35 could not identify any training-related improvement in emotion regulation. Training-related effects on self-control were investigated in one study.…”
Section: Executive Regulationmentioning
confidence: 97%
See 3 more Smart Citations
“…39 Of the four studies that found no effect, three used a web-based application and one applied a DVD program. 36 In addition to the lack of effect on inhibition, Polsinelli et al 35 could not identify any training-related improvement in emotion regulation. Training-related effects on self-control were investigated in one study.…”
Section: Executive Regulationmentioning
confidence: 97%
“…Within the studies included, digital mindfulness training programs were investigated in children/adolescents, 34 older people, [35][36][37] as well as adults. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Participants in all studies reported no physical, neurological, and/or psychological disabilities.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies included parameters that could not be assigned to either of the ve categories. Verbal uency was addressed in two studies but neither could identify signi cant intervention-related effects (Tam et al, 2017;Wahbeh et al, 2016).…”
Section: Other Cognitive Functionsmentioning
confidence: 99%